Answer:
3)5x-4y=-3
6x+4y=14
Step-by-step explanation:
The system of equations is given
5x-4y=-3
3x+2y=7
Multiplying both sides of the lower equation by 2, we get
6x + 4y = 14
That means your answer 3)
<span><span>Equation:- 45+<span><span>5/6 </span>x</span></span>=50
</span>1) Simplify both sides of the equation. <span><span><span><span>5/6 </span>x </span>+ 45 </span>= 50
</span>2) Subtract 45 from both sides. <span><span><span><span><span>5/6 </span>x </span>+ 45 </span>− 45 </span>= <span>50−45 </span></span><span><span><span>5/6 </span>x</span>=5
</span>3) Multiply both sides by 6/5.<span><span><span>(<span>6/5</span>)</span>*<span>(<span><span>5/6 </span>x</span>)</span></span>=<span><span>(<span>6/5</span>)</span>*<span>(5)</span></span></span><span>x=6
SO, x=6.
</span>
Hope I helped.
Answer:
what is the question because I don't understand what you mean
It's equals 1 1/3 that's the correct answer